2012
DOI: 10.2147/opth.s33816
|View full text |Cite
|
Sign up to set email alerts
|

Effects of BAK-free travoprost treatment for 3 years in patients with normal tension glaucoma

Abstract: BackgroundThe purpose of this study was to evaluate the effects of benzalkonium (BAK)-free travoprost monotherapy administered for 3 years on intraocular pressure and visual field performance.MethodsThe intraocular pressure of 76 patients with normal tension glaucoma was monitored every 1–3 months. A Humphrey visual field test was performed every 6 months after treatment and compared with the results before treatment. Visual field performance was also evaluated by trend and event analysis.ResultsThirty cases d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Travoprost with sofZia® use has been reported in limited numbers of NTG patients, with a potent IOP lowering effect and minimal corneal damage. 12 , 13 We, therefore, expanded on these findings and conducted a study with a large number of Japanese NTG patients.…”
Section: Discussionmentioning
confidence: 99%
“…Travoprost with sofZia® use has been reported in limited numbers of NTG patients, with a potent IOP lowering effect and minimal corneal damage. 12 , 13 We, therefore, expanded on these findings and conducted a study with a large number of Japanese NTG patients.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, Suh et al reported an 18.8%–25.1% IOP reduction with travoprost in 45 patients with unilateral NTG after 12 months of treatment 8. In the longest-term follow-up, Inoue et al recently reported a 16% IOP reduction with travoprost in NTG patients at 3 years 7. In a randomized controlled trial, Ang et al analyzed the effect of travoprost on diurnal IOP (8 am to 5 pm) in 54 NTG patients 9.…”
Section: Discussionmentioning
confidence: 99%
“… 8 In the longest-term follow-up, Inoue et al recently reported a 16% IOP reduction with travoprost in NTG patients at 3 years. 7 In a randomized controlled trial, Ang et al analyzed the effect of travoprost on diurnal IOP (8 am to 5 pm) in 54 NTG patients. 9 At 6 months, the average diurnal IOP was significantly reduced by 16.1%, with only 32.9% achieving an IOP reduction >20%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adverse effects associated with these preservatives seem to be more significant for glaucoma patients, mainly because of their chronic use of one or more preservative-containing agents [ 6 ]. Therefore, considerable efforts have been made in the recent years by pharmaceutical companies to develop less toxic glaucoma medications such as preservative-free preparations [ 7 ].…”
mentioning
confidence: 99%